Use of 18F-FDG-PET/CT in differential diagnosis of primary central nervous system lymphoma and high-grade gliomas: A meta-analysis - Zhang, Guisheng; Li, Jiuhong; Hui, Xuhui (Frontiers in Neurology, 2022)
Background: Primary central nervous system lymphoma (PCNSL) and high-grade glioma (HGG) appear similar under imaging. However, since the two tumors vary in their treatment methods, their differential diagnosis is crucial. The use of 18F-fluorodeoxyglucose positron emission tomography computed tomography (18F-FDG-PET/CT) imaging to effectively distinguish between the two tumors is not clear; therefore, a meta-analysis was carried out to determine its effectiveness. Materials and Methods: The databases PubMed, EMBASE, Cochrane, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang, China Science, and Technology Journal Database (CQVIP) were exhaustively searched using stringent inclusion and exclusion criteria to select high-quality literature. The Quality Assessment Tool for Diagnostic Accuracy Studies (QUADAS-2) was used for the qualitative assessment of the included literature. The bivariate effect model was used to combine statistics such as sensitivity (SEN) and specificity (SPE), positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR) (95% confidence intervals (CI)), plot summary receiver operating characteristic (SROC) curve, and calculate the area under the curve (AUC) value. Sensitivity analysis was used to evaluate the stability of the results, and Deek’s test was used to assess publication bias. Meta-regression and subgroup analysis was used to determine the sources of heterogeneity. Results: A total of nine studies were included in this study. For differential diagnosis of PCNSL and HGG, the combined SEN was 0.91 (95% CI: 0.80–0.96; I2 = 46.73%), combined SPE was 0.88 (95% CI: 0.82–0.93; I2 = 56.30%), the combined PLR was 7.83 (95% CI: 4.96–12.37; I2 = 15.57%), combined NLR was 0.10 (95% CI: 0.05–0.23; I2 = 31.99%), combined DOR was 77.36 (95% CI: 32.74–182.77; I2 = 70.70%). The AUC of SROC was 0.95 (95% CI 0.93–0.97). No publication bias was found and the sample size and different parameters were the primary reason for heterogeneity. Conclusion: The 18F-FDG-PET/CT imaging technique has a high diagnostic accuracy in the differential diagnosis of PNCSL and HGG. Patients suspected to have the above two tumors are suggested to be examined by 18F-FDG-PET / CT to help in the clinical distinction and further treatment modalities.